Penulisan “Proximate Cause” dan “but for test” Sebagai Sebab Mati dalam Sertifikat Kematian - Basbeth, Ferryal (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
It is often difficult for a doctor to write off the death certificate because when death occurs due to woundcomplications that occur due to the killing of more than one year prior to death.In an old law in England known the term "year and a day rule", which says that death is believed to occur morethan one year and one day, there is no connection with the murder, now it's been much written off in manycountries, including the United States and New Zealand.The basis for this rule is the elimination of intervention efficacy in prolonging the life of a person's doctor andtech support, so that the interval between the act of murder and death that ensues is also elongated. In addition,advances in forensic medicine to assist the court in determining a cause of death although the action is carriedout long enough in the past.The series of events that occur in delayed death due to homicide (delayed Homicide) are rarely reported. Generaldeath in murder cases pending include: infected decubitus ulcers, bronchopneumonia, and urosepsis due toparalysis due to spinal cord trauma, seizures follow-up post-blunt head injury, and small bowel adhesion / herniadue to stab wounds. In making a determination of death is consistent and accurate information on the pendingmurder case, it is important to rely on the definition of a direct cause of death pending kematian.Penyelidikancase of murder to be a challenge due to: failure to report the death to the authorities, the lack of adequatedocumentation of trauma that occurred, and jurisdictional differences between the trauma and death.
Keywords: Cause of death, Proximate Cause, but for test